Experimental studies for the personalized application of boron neutron capture therapy to the treatment of cutaneous melanoma - Carpano, Marina; Santa Cruz, Gustavo Alberto; Rodriguez, Carla; Nievas, Susana Isabel; Olivera, María Silvina; Perona, Marina; Boggio, Esteban Fabián; Longhino, Juan Manuel; Pisarev, Mario Alberto; Juvenal, Guillermo Juan; Dagrosa, María Alejandra (AME Publishing Company, 2021)
Fil: Carpano, Marina. Comisión Nacional de Energía Atómica; Argentina